Relationship between smoking and the incidence of sarcopenia: The SarcoPhAge cohort. (April 2021) - Locquet, M.; Bruyère, O.; Lengelé, L.; Reginster, J.Y.; Beaudart, C.
Abstract: Introduction: The association of tobacco use and incidence of muscle impairments has not been extensively explored in research. In this study, the relationship between smoking and the incidence of sarcopenia is investigated. Methods: The present longitudinal study used data from the Sarcopenia and Physical Impairment with advancing Age (SarcoPhAge) cohort, which includes older adults aged ≥65 years. All individuals with follow-up data on muscle health were included in this post hoc analysis. A diagnosis of sarcopenia was established, at each year of follow-up, according to the European Working Group on Sarcopenia in older People 2 (EWGSOP2) criteria. A sensitivity analysis was performed using other diagnostic criteria for sarcopenia. The smoking status and the number of cigarettes smoked per day were self-reported. The relationship between smoking status or the number of cigarettes smoked per day and the incidence of sarcopenia/severe sarcopenia throughout the 5 years of follow-up was evaluated using the Cox proportional hazards model. Results: In total, the study population included 420 participants, with a median age of 71.7 years (P25–P75 = 67.7–76.9 years) and 59.8% were female. Over the 5 years of follow-up, 78 participants (18.6%) became sarcopenic as per the EWGSOP2 criteria and 41 individuals (9.8%) developed severe sarcopenia. There were significantly more smokers than non-smokers who developed sarcopenia (35.9% vs 16.8%, P -value = 0.003). A fully adjusted Cox model confirmed this observation, yielding a hazard ratio of 2.36 (95% confidence interval [CI]: 1.31–4.26), meaning that smokers have a 2.36-fold higher risk of developing sarcopenia. Furthermore, individuals who smoked had a 2.68 times increased risk of developing severe sarcopenia (95% CI: 1.21–5.93) than those who did not smoke. Sensitivity analyses globally confirmed these findings when applying other diagnostic criteria for sarcopenia. Discussion: Smoking seems to be an important predictor for the onset of sarcopenia, highlighting, once again, that tobacco use is a major public health problem. Highlights: Sarcopenia represents a major public health problem among older individuals. This study verified the impact of tobacco consumption on the incidence of sarcopenia. Smoking significantly increased the risk of developing sarcopenia. Each additional cigarette consumed per day increased the risk of developing sarcopenia. Public health leaders must continue the fight against smoking to protect muscle health in older individuals.